Individual, Group, and Organizational Factors Affecting Group Bidding Decisions for Construction Projects - Peng Yan; Junying Liu; Martin Skitmore (Advances in Civil Engineering)
Deciding whether bid for the construction project is classic risk-based decision-making that is crucial to the survival and prosperousness of construction companies. More contractors are adopting group bidding decision-making to reduce the number of incorrect decisions. However, previous related studies mainly focus on project factors that overlook the members of bidding groups and the interaction between bidding group members. The aim of this paper, therefore, is to investigate the potential factors that influence group bidding decision-making for construction projects. Twenty factors relating to individual, group, and organizational levels are identified through a literature review and interviews with experienced practitioners. A questionnaire survey of 203 Chinese international contractors is conducted to obtain the importance of the factors involved. The results of the ranking analysis indicate 14 critical factors, among which “risk perception” and “team decision preference” are regarded as the two most significant. Moreover, 20 factors can be classified into five groupings: (1) values and strategic goals, (2) collaboration and learning orientation, (3) consensus reaching, (4) risk awareness, and (5) empowerment and development, with risk awareness having an especially strong influence. This research deepens the understanding of factors belonging to different organizational levels that need to be highlighted during the group bidding decision-making process and provides strategies for bidding groups and their companies to improve their decision performance.